2015
DOI: 10.1016/j.mgene.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis among male and female Jojoba genotypes employing gene targeted molecular markers, start codon targeted (SCoT) polymorphism and CAAT box-derived polymorphism (CBDP) markers

Abstract: To detect genetic variations among different Simmondsia chinensis genotypes, two gene targeted markers, start codon targeted (SCoT) polymorphism and CAAT box-derived polymorphism (CBDP) were employed in terms of their informativeness and efficiency in analyzing genetic relationships among different genotypes. A total of 15 SCoT and 17 CBDP primers detected genetic polymorphism among 39 Jojoba genotypes (22 females and 17 males). Comparatively, CBDP markers proved to be more effective than SCoT markers in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 44 publications
(54 reference statements)
7
33
1
Order By: Relevance
“…In contrast, the average Rp value of the CBDP markers was more than that of the SCoT markers, which indicated the high ability of the CBDP markers to reflect the genetic diversity in T. urartu. These results are in agreement with Heikrujam et al [36], Tiwari et al [9], Etminan et al [16,17,37] and Qaderi et al [19], who reported that SCoT and CBDP markers were more useful for dissecting genetic diversity and structure than other molecular marker techniques.…”
Section: Resultssupporting
confidence: 90%
“…In contrast, the average Rp value of the CBDP markers was more than that of the SCoT markers, which indicated the high ability of the CBDP markers to reflect the genetic diversity in T. urartu. These results are in agreement with Heikrujam et al [36], Tiwari et al [9], Etminan et al [16,17,37] and Qaderi et al [19], who reported that SCoT and CBDP markers were more useful for dissecting genetic diversity and structure than other molecular marker techniques.…”
Section: Resultssupporting
confidence: 90%
“…The SCoT primers are based on conserved regions flanking the initiation codon sequences of genes and CDDPs are short primers to generate useful genetic markers across functional domains of well-characterised plant genes (Collard, Mackill 2009a;Collard, Mackill 2009b). These marker techniques has been successfully employed in genetic diversity analysis of several plants, such as chickpea (Pakseresht et al 2013), wheat (Hamidi et al 2014), ramie (Satya et al 2015) and jojoba (Heikrujam et al 2015). The aim of the present study was to investigate the gentic diversity in Iranian landrace durum wheat accessions and examine the relationships of geographical sources of these accessions with their genetic diversity pattern.…”
Section: Introductionmentioning
confidence: 99%
“…When raised through seeds, about 50% or more of the seedlings are males [ 53 ]. The sex can be recognized only when the plants start bearing after 3–4 years of planting, while for an efficient commercial yield, no more than a 10% male population is required [ 54 ]. The success of jojoba growers, and indeed of the entire jojoba industry, depends upon the selection of high-yielding genotypes and their multiplication through vegetative means.…”
Section: Agronomy Aspects and Nutrient Requirements And Diseases Of Tmentioning
confidence: 99%
“…The present cultivations of this plant are mainly via vegetative propagation from a limited number of selected landraces which are consequently used in the cultivation of many more varieties. The large-scale cultivation of such genetically constant cultivars has resulted in a progressively less genetic bias for the crops, leading to genetic vulnerability [ 54 ]. For more maintainable and valuable production of jojoba, understanding the extent and association of genetic variations and their relationships is essential.…”
Section: Genetic Diversity and Molecular Biology Approachesmentioning
confidence: 99%